2015
DOI: 10.1083/jcb.201506103
|View full text |Cite
|
Sign up to set email alerts
|

The synaptonemal complex is assembled by a polySUMOylation-driven feedback mechanism in yeast

Abstract: Synaptonemal complex (SC) assembly requires polySUMOylation of Ecm11, which promotes polymerization of Zip1, the transverse filament, whereas the N terminus of Zip1 activates Ecm11 polySUMOylation, suggesting that this positive feedback loop underpins SC assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 40 publications
(60 reference statements)
1
42
0
Order By: Relevance
“…These state changes may best be explained by post-translational modifications of SC subunits (or the chromosome axes which they join), including, but not limited to, phosphorylation [39] and SUMOylation [40]. Alternatively, the binding and release of additional proteins to the SC could also function in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…These state changes may best be explained by post-translational modifications of SC subunits (or the chromosome axes which they join), including, but not limited to, phosphorylation [39] and SUMOylation [40]. Alternatively, the binding and release of additional proteins to the SC could also function in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that other members of the Ndt80 regulon are dispensable for SC destruction, strongly suggesting that the means to destroy the SC exists before pachytene exit but is unable to act in the absence of Cdc5 activity. Emphasis should be placed on identifying the targets of Cdc5, which likely include Red1 and/or Zip1, and possibly other central element proteins that are required for SC formation such as Ecm11 and Gmc2 (Humphryes et al , ; Voelkel‐Meiman et al , ; Leung et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…al (2015) demonstrated that Zip1's N terminal 346 residues is sufficient to promote Ecm11 SUMOylation in vegetative (non-meiotic) cells, provided that Gmc2 is also expressed. These data suggest that the N terminal region of Zip1 is able to engage with the Ecm11-Gmc2 proteins, perhaps in a direct manner or perhaps indirectly through a protein expressed in both meiotic as well as mitotic cells [51]. Similar to the uncertainty about whether Zip3 interacts with Zip1 in a direct manner, apart from the genetic interactions found for Zip1 and Ecm11 and the coincidence of Ecm11 and Gmc2 at the midline of SC (where Zip1 N termini also reside [19]), strong evidence of a direct physical interaction between Zip1 and Ecm11 or Gmc2 does not yet exist.…”
Section: Two Functionally Distinct Regions Within Zip1's N Terminal Tmentioning
confidence: 88%
“…We previously demonstrated that zip1[D21-163] phenocopies the ecm11 and gmc2 null mutant phenotype (a failure in SC assembly but proficiency in MutSg crossing over), suggesting that this N terminal region of Zip1 functionally interacts with the central element in order to assemble SC [22]. Moreover, Leung et. al (2015) demonstrated that Zip1's N terminal 346 residues is sufficient to promote Ecm11 SUMOylation in vegetative (non-meiotic) cells, provided that Gmc2 is also expressed.…”
Section: Two Functionally Distinct Regions Within Zip1's N Terminal Tmentioning
confidence: 99%